Th22 cells control colon tumorigenesis through STAT3 and Polycomb Repression complex 2 signaling. (2nd August 2016) - Sun, Danfeng; Lin, Yanwei; Hong, Jie; Chen, Haoyan; Nagarsheth, Nisha; Peng, Dongjun; Wei, Shuang; Huang, Emina; Fang, Jingyuan; Kryczek, Ilona; Zou, Weiping
ABSTRACT: Th22 cells traffic to and retain in the colon cancer microenvironment, and target core stem cell genes and promote colon cancer stemness via STAT3 and H3K79me2 signaling pathway and contribute to colon carcinogenesis. However, whether Th22 cells affect colon cancer cell proliferation and apoptosis remains unknown. We studied the interaction between Th22 cells and colon cancer cells in the colon cancer microenvironment. Colon cancer proliferation was examined by flow cytometry analysis and H 3 thymidine incorporation. Cell cycle related genes were quantified by real-time PCR and Western blotting. We transfected colon cancer cells with lentiviral vector encoding specific gene shRNAs and used chromatin immunoprecipitation (ChIP) assay to determine the genetic signaling involved in interleukin (IL)-22-mediated colon cancer cell proliferation. We showed that Th22 cells released IL-22 and stimulated colon cancer proliferation. Mechanistically, IL-22 activated STAT3, and subsequently STAT3 bound to the promoter areas of the Polycomb Repression complex 2 (PRC2) components SUZ12 and EED, and stimulated the expression of PRC2. Consequently, the activated PRC2 catalyzed the promoters of the cell cycle check-point genes p16 and p21, and inhibited their expression through H3K27me3-mediated histone methylation, and ultimately caused colon cancer cell proliferation. Bioinformatics analysis revealed that the levels of IL-22 expression positively correlated with the levels of genes controlling cancer proliferation and cell cycling in colon cancer. In addition to controlling colon cancer stemness, Th22 cells support colon carcinogenesis via affecting colon cancer cell proliferation through a distinct histone modification.